The Results of the Pilot Implementation of Criterion-Based Assessment of Professionally Oriented Linguistic Competence of Future Physicians - Valentyna Kushnir (Pedagogical Discourse, 2015)
In the article the results of the formative experiment to introduce the criterion-based assessment of professionally oriented linguistic competence of future physicians into the educational process are analyzed. On the basis of theoretical analysis of publications and researches of modern scientists approaches for essence interpretation of professionally oriented linguistic competence of future specialists such as competence, axiological, culturological and activity approaches are characterized. The essence of the professionally oriented linguistic competence of future physicians is defined. The components and indicators of the studied phenomenon such as cognitive and semantic, operating and activity , motivational and value, emotional and willful, professional and communicative components are characterized. The pedagogical conditions of professionally oriented linguistic competence formation of future physicians are presented and described such as presence of normative and legal base; presence of the educational and methodical providing; training of teaching staff; students interiorization of the physician professional role; positive co-operation in study groups; use of forms and methods of study based on high activity and personal students involvement into the educational process; dialogic approach in teacher-student co-operation. The content of criterion-based assessment of the phenomenon is shown. It consists of three testing parts and is used during three modules of study and control of «Professional English in general medicine» course. The validity of the results of testing of criterion-based assessment of professionally oriented linguistic competence of future physicians is proved. The results of the experiment have revealed significant positive statistically important differences between two controls of the experiment. It is indicated that the high level of the professionally oriented linguistic competence formation of future physicians has increased by one third from the general number of students taking part in the experiment. It testifies the effectiveness of criterion-based assessment system of future physicians professionally oriented linguistic competence. The realized study expands scientific knowledge of future physicians professionally oriented linguistic competence investigation and formation.